Стратегия развития предприятий экотуризма как фактор повышения их конкурентоспособности. - Безуглая, Людмила Сергеевна; Безугла, Людмила Сергіївна; Bezuhla, Liudmyla (Одеський національний університет, 2019)
У статті розглянуті проблеми ведення підприємництва у сфері екологічного туризму; виділені п'ять основних критеріїв, яким повинні відповідати підприємства екологічного туризму. Зазначено вплив екологічного туризму на соціально-економічні показники країни, які можуть бути надзвичайно значущі особливо для сільської місцевості України. Графічно відображені фактори соціально-економічного впливу на розвиток підприємств екотуризму в Україні, які приведуть до підвищення економічної стійкості територій, залучених до розвитку екологічного туризму в сільській місцевості за рахунок створення нових робочих місць; залучення у сферу обслуговування місцевого населення та підвищення їх життєвого рівня; зниження рівня соціальної напруженості. Проаналізовано позитивні та негативні аспекти діяльності підприємств екотуризму. Розглянуто основні напрями стратегії розвитку підприємств екологічного туризму з метою підвищення прибутковості та конкурентоспроможності. In the near future, ecotourism enterprises will receive priority development, taking into account their orientation towards the rational use of natural, historical and cultural objects; education of the population ecological outlook that will avoid many negative effects of mass tourism. In addition, the experience of foreign countries shows that eco-tourism enterprises contribute to social and economic development as a whole. The article deals with the problems of doing business in the field of ecological tourism; identified five main criteria to be met by companies ecotourism. Eco-tourism enterprises are usually understood as active and informative recreation of people visiting ecologically clean places, natural reservations, national parks and reserves, balneological institutions. The influence of ecological tourism on the socio-economic indicators of the country, which can be extremely significant especially for the rural areas of Ukraine, is indicated. For the formation of a positive image of enterprises in the territories of ecotourism, it is necessary to have a set of factors of effective functioning: a sufficient degree of economic development, the formation and development of infrastructures, services, transport, environmental component, the presence of recreational resources and the overall investment attractiveness. Displayed graphically factors of socio-economic impact on the development of eco-tourism enterprises in Ukraine, which will lead to increased economic stability of the territories involved in the development of eco-tourism in rural areas through the creation of new jobs; attracting local people to the service sector and raising their standard of living; reduce social tensions. The main directions of the development strategy for eco-tourism enterprises have been developed with the aim of increasing profitability and competitiveness. For the development of eco-tourism enterprises need a real look at their prospective profitability, competitiveness of services offered, as well as the possibility of their promotion. To do this, it is important to optimize the level of development of ecological tourism enterprises (travel multiplier) for the area and to develop a strategy leading to the achievement of this level.
Стратегія розвитку підприємств екотуризму як фактор підвищення їх конкурентоспроможності.
Ecotourism development strategy as the factor of increasing their competitiveness
Keywords: підприємства екологічного туризму; eco-tourism enterprises; стратегія розвитку підприємств; enterprise development strategy; соціально-економічний розвиток; socio-economic development; соціально-економічний вплив; socio-economic impact; конкурентоспроможність; competitiveness